Genome-Wide Association Study of Male Sexual Orientation. Issue 1 (December 2017) - Sanders, Alan; Beecham, Gary; Guo, Shengru; Dawood, Khytam; Rieger, Gerulf; Badner, Judith; Gershon, Elliot; Krishnappa, Ritesha; Kolundzija, Alana; Duan, Jubao; Gejman, Pablo; Bailey, J.; et al.
Abstract Family and twin studies suggest that genes play a role in male sexual orientation. We conducted a genome-wide association study (GWAS) of male sexual orientation on a primarily European ancestry sample of 1, 077 homosexual men and 1, 231 heterosexual men using Affymetrix single nucleotide polymorphism (SNP) arrays. We identified several SNPs withp < 10−5, including regions of multiple supporting SNPs on chromosomes 13 (minimump = 7.5 × 10−7 ) and 14 (p = 4.7 × 10−7 ). The genes nearest to these peaks have functions plausibly relevant to the development of sexual orientation. On chromosome 13, SLITRK6 is a neurodevelopmental gene mostly expressed in the diencephalon, which contains a region previously reported as differing in size in men by sexual orientation. On chromosome 14, TSHR genetic variants in intron 1 could conceivably help explain past findings relating familial atypical thyroid function and male homosexuality. Furthermore, skewed X chromosome inactivation has been found in the thyroid condition, Graves' disease, as well as in mothers of homosexual men. On pericentromeric chromosome 8 within our previously reported linkage peak, we found support (p = 4.1 × 10−3 ) for a SNP association previously reported (rs77013977, p = 7.1 × 10−8 ), with the combined analysis yieldingp = 6.7 × 10−9, i.e., a genome-wide significant association.